2018
DOI: 10.3390/molecules23061450
|View full text |Cite
|
Sign up to set email alerts
|

In-Syringe Micro Solid-Phase Extraction Method for the Separation and Preconcentration of Parabens in Environmental Water Samples

Abstract: In this study, a simple, rapid and effective in-syringe micro-solid phase extraction (MSPE) method was developed for the separation and preconcetration of parabens (methyl, ethyl, propyl and butyl paraben) in environmental water samples. The parabens were determined and quantified using high performance liquid chromatography and a photo diode array detector (HPLC-PDA). Chitosan-coated activated carbon (CAC) was used as the sorbent in the in-syringe MSPE device. A response surface methodology based on central c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The values in the desirability profile (Fig. 8 ) that are closer to 1.0 imply that the corresponding parameter or variable condition is optimum 37 . The optimum conditions for simultaneous preconcentration of As(III), Cd(II), Cr(III), Co(II), Ni(II), and Pb(II) ions were selected to be 6.5, 84 mg, 10 min, and 2.0 mol L −1 for sample pH, mass of adsorbent, extraction time and eluent concentration, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…The values in the desirability profile (Fig. 8 ) that are closer to 1.0 imply that the corresponding parameter or variable condition is optimum 37 . The optimum conditions for simultaneous preconcentration of As(III), Cd(II), Cr(III), Co(II), Ni(II), and Pb(II) ions were selected to be 6.5, 84 mg, 10 min, and 2.0 mol L −1 for sample pH, mass of adsorbent, extraction time and eluent concentration, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…The optimisation results were analysed using the analysis of variance (ANOVA), response surface methodology and desirability function in order to determine the significant factors, interaction effects and desirable conditions for optimum extraction [68]. The analysis of variance is reported in the form of a Pareto chart ( Figure 5), where the redline is indicative of the 95% confidence interval that a factor has significant effect on the extraction of trenbolone using the MIP [69].…”
Section: Multivariate Optimisationmentioning
confidence: 99%
“…Until now, different kinds of adsorbents have been used for extraction and preconcentration of PPCPs. These include multi-walled carbon nanotubes [ 33 ], nanofibers [ 27 , 28 , 34 ], graphene oxide nanocomposites [ 19 , 35 ], biopolymer-based composites [ 36 , 37 ], activated carbon, metal–organic frameworks [ 2 , 38 ] and metal oxide nanocomposites [ 28 ]. Recently, our previous research prepared a biodegradable superabsorbent based on a magnetic mesoporous carbon/β-cyclodextrin–chitosan (MMPC/CycChit) nanocomposite for removal of fluoroquinolones (FQs) from environmental samples [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The method was based on dispersive magnetic solid-phase extraction (DMSPE) based on the previously reported MMPC/CycChit adsorbent combined with high-performance liquid chromatography with diode array detection (HPLC-DAD). The choice of analytes to be investigated was based on the previous studies which revealed that anticonvulsants, beta-blockers, parabens and fluoroquinolones (FQs) are frequently detected in South African water systems [ 7 , 31 , 36 , 44 , 45 ]. The experimental factors (mass of adsorbent, eluent type, eluent volume, extraction time, desorption time and sample pH) affecting the extraction and preconcentration procedure were optimized using univariate and multivariate approaches.…”
Section: Introductionmentioning
confidence: 99%